Building marketing strategies by capitalizing on consumer trust issues, product boycotts and brand awareness - Wiyanti, Sari; Wicaksana, Muhammad sIddik Erdi; Budiyanto, Muhamad Andi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2024)
The conflict between Israel and Palestine has impact on the issue of trust, product boycotts and public awareness to leave pro-Israel products hit the world community, especially the people of Indonesia. Research method the approach used quantitative approach, with population is domestic companies and MSMEs located in Tegal. The sample of 34 respondents with non-probability sampling techniques and accidental sampling methods. The collected priner data will be analyzed statistically using SPSS 25, then analyzed by multiple linear regression and hypothesis testing, namely the t test, F test, and the coefficient of determination. Result the reseach is the Consumer Trust Issue has positive value of 0.979, the t test results with tcount value of 9.817>1.696, significant value of 0.000<0.05, which means H1 is accepted; Boycott Pro-Israel Product has positive value of 0.515, the t test results with tcount value of 2.451>1.696 significant value of 0.020<0.05, which means H2 is accepted; The Brand Awareness has positive value of 0.613; the t test results with tcount value of 2.473>1.696 with significant value of 0.019> 0.05 which means H3 is accepted. The results of the F test obtained an Fcount value of 54.670>2.69 with a significance value of 0.000<0.005, meaning that H4 is accepted.